Toda la sangre formando un río:1 Contributions to the histories of metal music studies from the Spanish-speaking world. (1st March 2022) - Varas-Díaz, Nelson; Hickam, Brian; González-Martínez, Susana; Castañeda, Mario; Galicia Poblet, Fernando; Nieves Molina, Alfredo; Scaricaciottoli, Emiliano
The field of metal music and culture studies is rapidly growing throughout the world. Efforts to document its history and development have emerged via publications in academic journals and edited books. Although this historical documentation of the emergence of an area of study is valuable, it has been geographically laden towards the Global North, and written by English-speaking scholars there. In this article, we aim to inform and balance that history-telling process through an exploration of contributions made from Spanish-speaking scholarly epicentres in the Global South. In doing so, we propose and implement a strategy that (1) surpasses the limitations of universalist approaches towards history by including contributions from epicentres of research in both the Global North and the Global South, (2) engages in a self-critical examination of the field of metal music studies, and asks scholars to examine why, and understand how, the disconnections between metal scholars in the Global North and the Global South come into existence and (3) recognizes that knowledge is developed through many mechanisms that bypass academic journals, monographs and traditional modes of academic writing. In order to understand how these three tenants are manifested in the Spanish-speaking world we present examples from Spain, Puerto Rico, Argentina, México, Guatemala and Perú. We recommend that future efforts to document the histories (in plural) of this area of study take into consideration scholarly efforts outside the Global North as a way to decolonize metal studies.